Kesalahan Siswa SMP Kelas VII dalam Menyelesaikan Soal Operasi Hitung Bilangan Pecahan (JURNAL PENELITIAN PENDIDIKAN MATEMATIKA, 2022)
This study aims to discover the types of fraction arithmetic operations and the factors that cause students to make mistakes in solving fractional arithmetic operations questions. This type of research is descriptive-qualitative research. The population in this study were class VII students of South Indralaya 1 Middle School, South Indralaya 2 Middle School, and South Indralaya 3 Public Middle School, with a total sample of 150 VII-grade students. The data collection technique was in the form of giving tests with as many as 12 questions as experts and interviews had validated. Data analysis used is data reduction, data presentation, and conclusions. The results showed that the most dominant type of fraction arithmetic operations in which students completing fraction arithmetic operations made mistakes was type 10 (a/b:c/d) 82 students, type 6 (c-a/b) 78 students, type 3 (c+a/b) 77 students, type 11 (c:a/b) 76 students, and type 12 (a/b:c) 71 students.